Digital Transformation of Archives through the SRIKANDI Application - Teku, Marici; Gobang, Jonas; Retu, Markus; Sedu, Viktor (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The digitalization of archive management represents a strategic step toward modernizing government administration. This study examines the implementation of the Integrated Dynamic Archival Information System (APLIKASI SRIKANDI) at the Regional Archives and Library Office of Sikka Regency. Key aspects explored include challenges in digital archive transformation, objectives of system integration, methodologies employed, and the outcomes achieved, alongside future prospects for improvement. The study highlights the role of Universitas Nusa Nipa students’ internship programs in supporting digital archive initiatives. The findings reveal that APLIKASI SRIKANDI has significantly improved the efficiency of archival management processes. However, technical limitations, inadequate technological infrastructure, and human resource constraints remain challenges. To address these issues, the study recommends enhancing infrastructure, offering comprehensive training programs, and developing inclusive digital communication strategies. These efforts aim to optimize system implementation and ensure sustainability in achieving a fully integrated archival management framework. This research underscores the importance of strategic planning and collaboration in driving successful digital transformation within the public sector.